Evaluation of Timing of Implant Placement in Maxillary Esthetic Zone with Type I Extraction Sockets- A Randomized Controlled Trial - Santhanakrishnan M; Subramanian V; Arul D; Marimuthu SV (Clinical, Cosmetic and Investigational Dentistry)
Muthukumar Santhanakrishnan,1 Vedavalli Subramanian,2 Devi Arul,2 Sri Vidhya Marimuthu2 1Faculty of Dental Sciences, Department of Periodontology, Sri Ramachandra Institute of Higher Education and Research, Chennai, Tamil Nadu, India; 2Department of Periodontology, Sri Ramachandra Institute of Higher Education and Research, Chennai, Tamil Nadu, IndiaCorrespondence: Muthukumar Santhanakrishnan, Department of Periodontology, Faculty of Dental Sciences, Sri Ramachandra Institute of Higher Education and Research, 1, Mount Poonamalle road, Sri Ramachandra Nagar, Chennai, Tamil Nadu, 600116, India, Tel +9884118681, Fax +044-24767008, 24765995, Email muthukumars@sriramachandra.edu.inPurpose: The present study aimed to evaluate the appropriate protocol to be followed in the maxillary esthetic zone involving single dental implants by comparing three implant placement protocols: immediate implant placement (IIP) with and without the socket shield technique (SST) and delayed implant placement (DIP) in terms of dynamic alterations in hard and soft tissues and patient-related outcome measures (PROMS).Materials and Methods: A total of 75 patients were recruited for the study and randomly allocated to the SST, IIP, and DIP groups (25 each). They were subjected to Cone Beam Computed Tomography (CBCT) assessment pre-operatively, 6 and 12 months post-operatively to evaluate changes in Crestal Bone Thickness (CBT). Soft tissue changes were evaluated using the pink aesthetic score (PES) and visual analogue scale (VAS) to assess the pain threshold and patient satisfaction.Results: There was a statistically significant difference in the mean reductions in crestal bone thickness (CBT) between and among the groups. The SST group demonstrated a significantly lower reduction in CBT (0.09) than the IIP and DIP groups, which showed a mean reduction in CBT of 0.18 and 0.50 at (p< 0.01), respectively, at the end of 12 months. However, when the mean differences in PES between the groups were compared, there was a statistically significant difference for SST 13(2), IIP 10(2), and DIP 9(2) (p< 0.01).Conclusion: Socket shield technique could be technique of choice for IIP when buccal bone thickness is < 1mm as demonstrated by less reduction in CBT and better PES at the end of 12 months than the IIP and DIP groups.Keywords: socket shield technique, single tooth dental implant, socket graft